CYCLIC NUCLEOTIDE-GATED ION CHANNEL 2 modulates auxin homeostasis and signaling. Issue 3 (27th July 2021) - Chakraborty, Sonhita; Toyota, Masatsugu; Moeder, Wolfgang; Chin, Kimberley; Fortuna, Alex; Champigny, Marc; Vanneste, Steffen; Gilroy, Simon; Beeckman, Tom; Nambara, Eiji; Yoshioka, Keiko
Abstract: Cyclic nucleotide-gated ion channels (CNGCs) have been firmly established as Ca 2+ -conducting ion channels that regulate a wide variety of physiological responses in plants. CNGC2 has been implicated in plant immunity and Ca 2+ signaling due to the autoimmune phenotypes exhibited by null mutants of CNGC2 in Arabidopsis thaliana . However, cngc2 mutants display additional phenotypes that are unique among autoimmune mutants, suggesting that CNGC2 has functions beyond defense and generates distinct Ca 2+ signals in response to different triggers. In this study, we found that cngc2 mutants showed reduced gravitropism, consistent with a defect in auxin signaling. This was mirrored in the diminished auxin response detected by the auxin reporters DR5::GUS and DII-VENUS and in a strongly impaired auxin-induced Ca 2+ response. Moreover, the cngc2 mutant exhibits higher levels of the endogenous auxin indole-3-acetic acid, indicating that excess auxin in the cngc2 mutant causes its pleiotropic phenotypes. These auxin signaling defects and the autoimmunity syndrome of the cngc2 mutant could be suppressed by loss-of-function mutations in the auxin biosynthesis gene YUCCA6 ( YUC6 ), as determined by identification of the cngc2 suppressor mutant repressor of cngc2 ( rdd1 ) as an allele of YUC6 . A loss-of-function mutation in the upstream auxin biosynthesis gene TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS ( TAA1, WEAK ETHYLENE INSENSITIVE8 ) also suppressed the cngc2 phenotypes, further supporting the tight relationship between CNGC2 and the TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS–YUCCA -dependent auxin biosynthesis pathway. Taking these results together, we propose that the Ca 2+ signal generated by CNGC2 is a part of the negative feedback regulation of auxin homeostasis in which CNGC2 balances cellular auxin perception by influencing auxin biosynthesis. Abstract : One-sentence summary: The immunity-related Ca 2+ channel CYCLIC NUCLEOTIDE-GATED CHANNEL 2 modulates auxin homeostasis and balances cellular auxin perception by influencing auxin biosynthesis.